Hexagonal Wilson loops in planar =4 SYM theory at finite coupling. (20th September 2016) - Basso, Benjamin; Sever, Amit; Vieira, Pedro
Abstract: We report on the complete OPE series for the 6-gluon MHV and NMHV amplitudes in planar  = 4 SYM theory. Namely, we provide a finite coupling prediction for all the terms in the expansion of these amplitudes around the collinear limit. These furnish a non-perturbative representation of the full amplitudes.